Analisis penyaluran zakat untuk meningkatkan kesejahteraan kaum dhuafa pada masyarakat Air Molek di lembaga LAZISWAF Khairul Ummah - Pidola, Viras Alti; Indriani, Meisya (STAI Auliaurrasyidin Tembilahan, 2025)
Zakat is a key instrument with a strategic role in wealth distribution and poverty alleviation. The effectiveness of zakat distribution in achieving these goals still requires in-depth analysis within the context of economic and social welfare. This study aims to analyze the distribution mechanism, identify changes in welfare levels, and evaluate zakat distribution towards improving welfare. The study used a qualitative descriptive approach supported by quantitative data. Data were obtained through interviews, field observations, and documentation. Analysis was carried out through data reduction, data presentation, and drawing conclusions with welfare indicators covering economic (income and employment), social (education and health), and spiritual (active worship and independence). The results show that LAZISWAF Khairul Ummah implements two forms of zakat distribution: consumptive zakat to meet basic needs and productive zakat in the form of business capital assistance. Zakat distribution has been proven to have a positive impact on improving the welfare of the poor, indicated by increased income, access to education, and social participation. However, long-term effectiveness still needs to be improved through mentoring programs and ongoing monitoring.